2009
DOI: 10.1002/hed.21014
|View full text |Cite
|
Sign up to set email alerts
|

Association between transforming growth factor β1 genetic polymorphism and response to chemoradiotherapy in head and neck squamous cell cancer

Abstract: Genetic polymorphism of the TGFB1 signal sequence is associated with the response to chemoradiotherapy. TGF-beta1 may sensitize cancer stem cells to chemoradiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 31 publications
(28 reference statements)
0
15
0
Order By: Relevance
“…This association could not be observed among patients who had no initial chemoradiotherapy but who primarily underwent initial surgery that was planned to be radical [10,11]. These patients had residual tumor immediately or within the next few weeks after the surgery.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…This association could not be observed among patients who had no initial chemoradiotherapy but who primarily underwent initial surgery that was planned to be radical [10,11]. These patients had residual tumor immediately or within the next few weeks after the surgery.…”
Section: Discussionmentioning
confidence: 61%
“…Of note is that our previous finding on the association between TGFb1 genotype and survival was restricted to patients who had undergone definitive chemoradiotherapy as the initial planned curative treatment [10,11]. This association could not be observed among patients who had no initial chemoradiotherapy but who primarily underwent initial surgery that was planned to be radical [10,11].…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Another study showed that TGF-β1 mRNA and TGF-β1 were overexpressed in tumor cells of scirrhous gastric cancer [21]. The TGF-β1 −509 C/T polymorphism have been shown to be associated with breast cancer survival in Chinese population [22,23] and chemoradiotherapy response in 175 Finnish patients with head and neck squamous cancer [24], respectively. A Korean study showed that the variant T genotype is associated with a reduced risk of lung cancer [25].…”
Section: Discussionmentioning
confidence: 99%